2016
DOI: 10.1080/0267257x.2016.1251956
|View full text |Cite
|
Sign up to set email alerts
|

Creative contests: knowledge generation and underlying learning dynamics for idea generation

Abstract: International audienceDue to the heterogeneous nature of the crowd in online crowdsourcing, one key question discussed by academics and practitioners is whether participants are skilled enough to make valuable contributions. This research studies learning processes underlying idea generation in creative contests. Based on qualitative findings triangulating participants’ and brands’ perspectives, we identify six incoming and outgoing user skills which contribute to the development of valuable contributions and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
25
0
5

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(31 citation statements)
references
References 61 publications
1
25
0
5
Order By: Relevance
“…Their ability to consider solutions outside the domain of existing brands suggests that they may develop innovative, proprietary solutions to the consumption situations and problems. Thus, the study reaffirms the innovative abilities of normal communities of consumers (Steils and Hanine, 2016; Yoshida et al, 2014), but we contend here that these innovative capabilities are utilised by consumers themselves, hence increasing their own resources outside of the market and empowering them. While marketing thought and practice of the last two decades has brought brand and the emotional and relational aspects of branding to the forefront of our thinking, the study shows how consumers may not easily connect their pragmatic everyday consumption problems with the brands they know.…”
Section: Discussionsupporting
confidence: 58%
See 1 more Smart Citation
“…Their ability to consider solutions outside the domain of existing brands suggests that they may develop innovative, proprietary solutions to the consumption situations and problems. Thus, the study reaffirms the innovative abilities of normal communities of consumers (Steils and Hanine, 2016; Yoshida et al, 2014), but we contend here that these innovative capabilities are utilised by consumers themselves, hence increasing their own resources outside of the market and empowering them. While marketing thought and practice of the last two decades has brought brand and the emotional and relational aspects of branding to the forefront of our thinking, the study shows how consumers may not easily connect their pragmatic everyday consumption problems with the brands they know.…”
Section: Discussionsupporting
confidence: 58%
“…Marketers with foresight may use autonomous online consumer communities as sources of ideas to develop alternative business models and launch them faster than other stakeholders in the ecosystem. An in-depth analysis of such communities may constitute an alternative to interactive crowdsourcing and some of its challenges (Djelassi and Decoopman, 2016; Steils and Hanine, 2016). For instance, marketers could also study the abovementioned thread on how users dry their clothes in a hot and humid climate in order to detect particular needs that are currently underserved, and for which they may be able to develop solutions.…”
Section: Discussionmentioning
confidence: 99%
“…Leur capacité à envisager des solutions hors du champ des marques existantes suggère qu’ils peuvent développer des solutions exclusives et innovantes face à des problèmes et situations de consommation. De cette façon, l’étude confirme les capacités d’innovation de simples communautés de consommateurs (Steils et Hanine, 2016; Yoshida et al, 2014). Néanmoins, dans le cas présent, nous soutenons que ces capacités d’innovation sont exploitées par les consommateurs eux-mêmes, augmentant ainsi leurs propres ressources en dehors du marché et renforçant leur pouvoir d’action.…”
Section: Discussionunclassified
“…Les marketers visionnaires peuvent exploiter les communautés de consommateurs en ligne autonomes comme sources d’idées pour développer des modèles économiques alternatifs et les lancer plus rapidement que les autres parties prenantes de l’écosystème. Une analyse approfondie de ces communautés pourrait constituer une alternative au crowdsourcing (production participative) interactif et à certains de ses enjeux (Djelassi et Decoopman, 2016; Steils et Hanine, 2016). A titre d’exemple, les marketers pourraient également étudier le fil de discussion évoqué précédemment sur la façon dont les utilisateurs font sécher leur linge sous un climat chaud et humide, afin de détecter des besoins particuliers qui sont actuellement insatisfaits et pour lesquels ils pourraient être en mesure de développer des solutions.…”
Section: Discussionunclassified
“…In the next section, this study discusses theories about how online interaction among participants is associated with their resulting contributions. Recent studies of online idea generation arise out of studies that focus on how organizations outsource a task to a large crowd through an open call for contributions [14,15,25]. Studies have shown that a large, diverse group of individuals can collectively generate creative ideas for companies.…”
Section: Ideas In Open Government Dialoguementioning
confidence: 99%